Ternary platinum alloy counter electrodes for high-efficiency dye-sensitized solar cells. (1st February 2016) - Yang, Qiming; Yang, Peizhi; Duan, Jialong; Wang, Xiaopeng; Wang, Lei; Wang, Zhongling; Tang, Qunwei
Graphical abstract: Highlights: Ternary Pt-M-Ni alloy CE catalysts are synthesized for DSSCs. The catalytic activity is markedly enhanced by alloying Pt with Ni and M. The DSSCs yield maximum efficiency of 8.71%. The stability of ternary alloy CE is markedly enhanced in comparison with Pt. Abstract: Theoretical understanding of the intrinsic mechanism for enhanced electrocatalytic activity and rational design for liquid-junction dye-sensitized solar cell (DSSC) are two persistent objectives in pursuing dual-functional counter electrode (CE) electrocatalysts with excellent electrochemical activity and stability. In the current work, we launch a strategy of synthesizing ternary platinum alloys (Pt-M-Ni, M = Co, Pd, Fe) CE and study on the synergistic effects of transition metals on catalytic activity. The preliminary results demonstrate that the ternary Pt-M-Ni alloy can markedly enhance the electrocatalytic behavior toward I3 −, yielding maximum 8.71% efficiency in the optimized DSSC platforms in comparison with 7.10% for pure Pt based device.